Pengaruh Fleksibilitas Jam Kerja dan Stres Kerja terhadap Integritas Karyawan di PT Bank Negara Indonesia Tbk - Muchamad Iqbaal Dwi Fajarianto; Elmira Siska; Natal Indra (Universitas 17 Agustus 1945 Semarang, 2023)
Employee integrity plays an important role in maintaining company trust and reputation. This study aims to analyze the effect of flexibility of working hours and work stress on employee integrity at PT Bank Negara Indonesia Inc. The purpose of this study was to analyze the effect of working hour flexibility and work stress on employee integrity at PT Bank Negara Indonesia Tbk, especially in the DGL (Digital Development) division in the mobile banking team. The research design adopted in this study is quantitative research with a descriptive approach. Data were collected from 33 respondents through questionnaires. The data were analyzed by carrying out instrument tests which include validity and reliability tests, classical assumption tests, then followed by multiple linear regression, partial tests, simultaneous tests and coefficient of determination tests. The results of this study show that partially, flexibility in working hours has a positive and statistically insignificant effect on employee integrity. Job stress has a negative and statistically significant effect on employee integrity. Simultaneously, both variables affect employee integrity at PT Bank Negara Indonesia Tbk. The results of this study have important implications for company management in developing strategies that improve employee integrity.